Using GIS to Manage Clean Water Supply System: A Case Study of Hoan Kiem District, Hanoi, Vietnam - Le, Thi Minh Phuong; Le, Thi Minh Huyen; Vu, Le Anh (International Journal of Sustainable Construction Engineering and Technology, 2024)
Managing clean water supply systems is the goal of many countries in the world, especially large cities in developing countries including Vietnam. In Vietnam, urban areas are facing many challenges in management such as building data sets and applying technology in management. Using smart management tools with large data sets will limit water loss, improve management efficiency, save costs and time. In Hanoi, there is still no synchronization of data and technology in managing clean water supply systems. The article shows the process of building a water supply system database, steps to normalize data on a mathematical basis and standardize spatial and attribute data. To introduce the process of building a GIS database on ArcGIS software to manage clean water in Hoan Kiem District, Ha Noi, Viet Nam. This is also a typical pilot for application in many other locations in different cities in Vietnam and can be connected to create big data in water supply management in many different cities in Vietnam.